Minutes of Finance and General Purposes Committee (extract) : International Brigade Dependants and Wounded Aid Committee
034-0160-001 MINUTE OF FINANCE AND GENERAL PURPOSES COMMITTEE, 25TH APRIL, 1938. 120. INTERNATIONAL BRIGADE DEPENDANTS AND WOUNDED AID COMMITTEE. The Secretary gave a report of the deputation from the International Brigade Dependants and Wounded Aid Committee to the National Council of Labour officers on 31st March, when requests were made for demonstrations, special conferences and deputations to the Prime Minister and Foreign Secretary. The report was NOTED. 292/946/34/160